Super absorbent resin
Patent Information
- Application Number
- JP2024546003
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-26
- Filing Date
- 2023-09-27
- Publication Date
- 2025-02-19
AI Technical Summary
【0010】 本発明の高吸水性樹脂は、吸収速度に優れているだけでなく、吸収および拡散性能に優れて再湿潤および漏出現象が少なく、吸収容量も優れている。したがって、前記高吸水性樹脂は、高い吸収性能および使用感を要求する吸水性物品に好適に用いることができる。
Smart Images

Figure 2025504998000001_ABST
Abstract
Description
[Technical field]
[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0123440 filed on September 28, 2022 and Korean Patent Application No. 10-2023-0129631 filed on September 26, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.
[0002] The present invention relates to a highly water-absorbent resin. [Background technology]
[0003] Super absorbent polymer (SAP) is a synthetic polymeric material that has the ability to absorb 500 to 1,000 times its own weight in water, and different companies that develop it give it different names, such as SAM (Super Absorbency Material) or AGM (Absorbent Gel Material). Such super absorbent polymers have started to be used in sanitary products, and are now widely used in materials such as soil water retention agents for gardening, water-stopping materials for civil engineering and construction, seedling sheets, freshness-preserving agents and poultices in the food distribution field.
[0004] Superabsorbent polymers used in sanitary products such as diapers are required to have a fast absorption rate, and research and development is being conducted to improve this rate. The absorption rate of superabsorbent polymers is usually evaluated through a vortex measurement method in which a certain amount of superabsorbent polymer is placed in physiological saline, stirred, and the time it takes for the vortex to disappear is measured. However, even if a superabsorbent polymer has an excellent vortex absorption rate, if the absorption is localized or the diffusion area is small, when the polymer is used in a diaper or the like, a rewet phenomenon may occur in which some of the absorbed liquid seeps out again when pressure is applied by the weight of the user. Conversely, if the diffusion area of the superabsorbent polymer is too large, there is a problem of leakage of liquid. Summary of the Invention [Problem to be solved by the invention]
[0005] SUMMARY OF THE PRESENT EMBODIMENTS An object of the present invention is to provide a highly absorbent polymer which not only has an excellent absorption rate, but also exhibits little rewetting and leakage when used in a diaper and has an improved absorption capacity. [Means for solving the problem]
[0006] According to one embodiment of the present invention, when a superabsorbent polymer is applied to the surface of a porous substrate to which saline solution (0.9 wt% NaCl aqueous solution) is continuously supplied, and the amount and absorption rate of saline solution absorbed by the superabsorbent polymer from the surface of the porous substrate are continuously measured from the time of application of the superabsorbent polymer, a superabsorbent polymer is provided in which i) the maximum absorption rate (Vmax) exceeds 0.4 g / g sec, ii) the time at which the maximum absorption rate is reached (Tmax) exceeds 5 seconds and is less than 120 seconds, and iii) the amount of saline solution absorbed by the superabsorbent polymer for 5 minutes (C5min) exceeds 40 g.
[0007] In one embodiment, i) the maximum absorption rate (Vmax) may be 0.45 g / g·sec to 1 g / g·sec.
[0008] In one embodiment, ii) the time at which the maximum absorption rate is reached (Tmax) may be between 8 seconds and 40 seconds.
[0009] In one embodiment, iii) the amount of saline solution absorbed by the superabsorbent polymer for 5 minutes (C5min) may be 45g to 55g. Effect of the Invention
[0010] The superabsorbent polymer of the present invention has not only excellent absorption speed but also excellent absorption and diffusion properties, resulting in less rewetting and leakage, and excellent absorption capacity. Therefore, the superabsorbent polymer can be suitably used in absorbent articles that require high absorption performance and usability. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 shows an embodiment of a measuring device capable of measuring the physical properties of the superabsorbent resin of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly indicates otherwise. In this specification, the terms "include", "comprise", "have" and the like are intended to specify the presence of an implemented feature, step, component, or combination thereof, and should be understood not to preclude the presence or additional possibility of one or more other features, steps, components, or combinations thereof.
[0013] Since the present invention can be modified in various ways and can have various forms, specific embodiments are illustrated and described in detail below, but it is not intended to limit the present invention to the specific disclosed forms, and it should be understood that the present invention includes any modifications, equivalents, or alternatives falling within the spirit and technical scope of the present invention.
[0014] The terminology used in this specification is for the purpose of referring to particular embodiments only and is not intended to be limiting of the present invention. And, as used herein, the singular forms "a," "an," and "the" include the plural forms unless the context clearly indicates otherwise.
[0015] In the drawings, parts that are not necessary for the explanation of the present invention are omitted in order to clearly explain the present invention, and the same reference numerals are used throughout the specification to refer to the same or similar components.
[0016] Super water absorbent resin According to one embodiment of the present invention, when a superabsorbent polymer is applied to the surface of a porous substrate to which saline solution (0.9 wt% NaCl aqueous solution) is continuously supplied, and the amount and absorption rate of saline solution absorbed by the superabsorbent polymer from the surface of the porous substrate are continuously measured from the time of application of the superabsorbent polymer, a maximum absorption rate (Vmax) exceeds 0.4 g / g sec, the time (Tmax) at which the maximum absorption rate is reached is between 5 seconds and less than 120 seconds, and the amount of saline solution absorbed by the superabsorbent polymer in 5 minutes (C5min) exceeds 40 g is provided.
[0017] As described above, a superabsorbent polymer having Vmax, Tmax, and C5min properties all falling within the specified ranges has excellent absorbency, absorption speed, rewetting, and leakage prevention properties, and therefore can provide an excellent feel when used in sanitary products such as diapers.
[0018] The Vmax, Tmax, and C5min are values measured at atmospheric pressure (760±50 mmHg) and at a temperature of 23° C. to 25° C., and the measurement method is described in more detail below.
[0019] The maximum absorption rate (Vmax) is related to the leakage prevention property of the superabsorbent polymer. Specifically, when Vmax exceeds 0.4 g / g·sec, the superabsorbent polymer can be judged to have excellent leakage prevention property. Preferably, Vmax is 0.45 g / g·sec or more, and more preferably 0.5 g / g·sec or more. The upper limit is not particularly limited, but may be 1 g / g·sec or less, for example.
[0020] The time (Tmax) at which the absorption rate reaches its maximum value is related to the diffusion performance of the superabsorbent polymer, specifically, the higher the local absorption capacity of the superabsorbent polymer, the shorter the Tmax appears. If the local absorption capacity of the superabsorbent polymer is too high, the area in which liquid diffuses within the superabsorbent polymer is narrowed, so that when the superabsorbent polymer is contained in a diaper, a rewet phenomenon may occur in which the liquid held in the superabsorbent polymer seeps out again due to pressure. On the other hand, if Tmax is too long, leakage may occur. In terms of diffusion performance, Tmax is preferably more than 5 seconds and less than 120 seconds, and more preferably 6 seconds or more, 8 seconds or more, or 10 seconds or more, and 60 seconds or less, 40 seconds or less, or 20 seconds or less.
[0021] The amount of saline solution absorbed by the superabsorbent polymer for 5 minutes (C5min) is related to the absorption capacity of the superabsorbent polymer, and the higher the absorption capacity of the superabsorbent polymer, the higher the C5min. If C5min is 40g or less, the absorption capacity of the superabsorbent polymer is insufficient, so the content of the superabsorbent polymer must be increased when applied to sanitary products such as diapers, and it is impossible to produce thin products. Therefore, C5min is preferably more than 40g, more preferably 42g or more, or 45g or more. Theoretically, the upper limit of C5min is not limited, but it may be, for example, 60g or less, or 55g or less.
[0022] The superabsorbent polymer according to one embodiment of the present invention may have a maximum absorption rate (Vmax) of 0.45 g / g sec to 1 g / g sec, a time to reach the maximum absorption rate (Tmax) of 8 to 40 seconds, and an amount of saline absorbed by the superabsorbent polymer for 5 minutes (C5min) of 42 g to 55 g.
[0023] The superabsorbent polymer according to one embodiment of the present invention may have a maximum absorption rate (Vmax) of 0.5 g / g sec to 1 g / g sec, a time to reach the maximum absorption rate (Tmax) of 10 to 20 seconds, and an amount of saline absorbed by the superabsorbent polymer for 5 minutes (C5min) of 45 g to 55 g.
[0024] The Vmax, Tmax, and C5min of the superabsorbent polymer can be determined by measuring the amount of saline absorbed by the superabsorbent polymer over time from the surface of a porous substrate to which physiological saline (0.9 wt% NaCl aqueous solution) is continuously supplied.
[0025] Since the existing physical property measurements of superabsorbent polymers are performed so that liquid absorption occurs on the entire surface of the superabsorbent polymer particles, there is a limit to predicting the actual absorption state of the superabsorbent polymer when it is contained in a product such as a diaper, and it is difficult to confirm the absorption area, diffusion performance, etc. of the superabsorbent polymer. In contrast, the Vmax, Tmax, and C5min are values measured assuming a case in which liquid absorption occurs on one surface of the superabsorbent polymer, as when the superabsorbent polymer is contained in an absorbent article such as a diaper, so that the various physical properties of the superabsorbent polymer when applied to a product can be grasped more reliably.
[0026] The porous substrate has a plurality of voids to contain the saline. When measuring the Vmax, Tmax, and C5min, the porous substrate is continuously supplied with saline from a saline supply source, and the voids on the surface are kept saturated with saline. When a superabsorbent polymer is applied onto such a porous surface, the superabsorbent polymer absorbs the saline that has filled the voids, and the voids are filled again with saline supplied from the saline supply source. That is, saline is continuously transferred from the saline supply source to the porous substrate and from the porous substrate to the superabsorbent polymer, and the amount of saline absorbed by the superabsorbent polymer is continuously measured over time, thereby measuring the Vmax, Tmax, and C5min.
[0027] The porous substrate may be, for example, a glass filter, specifically, a glass filter having an extra coarse porosity according to the ASTM standard.
[0028] The Vmax, Tmax, and C5min may be measured, for example, by a superabsorbent polymer physical property measuring device 100 as illustrated in Fig. 1. The superabsorbent polymer physical property measuring device 100 may include the following configuration.
[0029] Libra 13 and A first water tank 10 located on the balance 13; A second water tank 20 is located near the balance and has a glass filter 21 on the top. a cylinder 22 that is located on the glass filter 21 of the second water tank, has a mesh (not shown) on its lower surface that contacts the glass filter 21, and has an open upper surface; a connecting pipe 14 that connects the first water tank 10 and the second water tank 20 and transfers liquid from the first water tank 10 to the second water tank 20;
[0030] The first water tank 10 supplies saline 12 to the second water tank 20 and is located on a balance 13. The balance 13 may be connected to a computer PC so that the weight of the first water tank 10 can be continuously measured and recorded.
[0031] The size of the first water tank 10 can be selected depending on the amount of sample (super absorbent polymer) used. For example, when 0.1 g to 2.0 g of super absorbent polymer is used as a sample, the first water tank 10 should have an internal volume of 500 cm. 3 or more than 1000cm 3 Above 3000cm 3 or less than 2000cm 3 The shape and size of the first water tank 10 are not particularly limited, but a tall cylindrical or rectangular parallelepiped shape is preferable since it can more smoothly supply the physiological saline solution 12 to the second water tank 20. As an example, the first water tank 10 may have an inner diameter and height of 8 cm or more, or 10 cm or more, and 30 cm or less, or 20 cm or less, respectively, but is not limited thereto.
[0032] The first water tank 10 may have a structure in which all sides are closed, as shown in FIG. 1. In this case, a pipe 11, which is an air passage, may be provided to penetrate the upper surface of the first water tank 10 so that the internal pressure of the first water tank 10 can be maintained at atmospheric pressure (760±50 mmHg). Specifically, the upper end of the pipe 11 may be exposed to the atmosphere, and the lower end of the pipe 11 may be provided to be immersed below the surface of the physiological saline solution 12. When the first water tank 10 of the above-mentioned size is used, the inner diameter of the pipe 11 may be, but is not limited to, 4 to 6 mm, or 3 to 10 mm. The length of the pipe 11 may be appropriately adjusted depending on the depth of the water tank, etc.
[0033] The first water tank 10 and the second water tank 20 are connected through a connecting pipe 14, so that the physiological saline 12 filled in the first water tank 10 can be continuously supplied to the second water tank 20. In order to stably supply the physiological saline to the second water tank 20 when measuring the physical properties of the superabsorbent polymer, the connecting pipe 14 may be preferably located at a point less than half or less than one-third of the height of each water tank.
[0034] The inner diameter of the connecting pipe 14 may be, for example, in the range of 5 mm to 20 mm, or 10 to 15 mm. The diameter and length of the connecting pipe may be appropriately adjusted depending on the positions and sizes of the first water tank 10 and the second water tank 20.
[0035] The second water tank 20 has an internal volume smaller than that of the first water tank 10, so that the supply of physiological saline from the first water tank is not insufficient during measurement of the physical properties of the superabsorbent polymer. Preferably, the internal volume of the second water tank 20 is 30% or more, or 50% or more, and 95% or less, or 90% or less, or 85% or less of the internal volume of the first water tank 10.
[0036] A glass filter 21 is placed on the upper surface of the second water tank 20. A cylinder 22 with a mesh (not shown) on its underside and an open top is placed on the glass filter, and the superabsorbent polymer sample is applied onto the mesh of the cylinder. The glass filter 21 receives physiological saline from the second water tank 20 and serves to transfer it to the superabsorbent polymer sample 23. When the superabsorbent polymer absorbs the physiological saline from the glass filter, the absorbed amount moves from the first water tank to the second water tank and back to the glass filter, and the porous glass filter is supplied with physiological saline from the second water tank, which is constantly kept at a full water level, and is thereby maintained in a saturated state.
[0037] The glass filter 21 may constitute a part or the whole of the upper surface of the second water tank 20. The diameter of the glass filter may be appropriately selected depending on the amount of the sample, and for example, when 0.1 g to 2.0 g of a superabsorbent resin is used as the sample, the diameter of the glass filter 21 is preferably 50 mm or more, or 70 mm or more, and 200 mm or less, or 150 mm or less, or 130 mm or less.
[0038] In addition, it is preferable that the thickness of the glass filter 21 is 3 mm or more, or 5 mm or more, and 10 mm or less, or 9 mm or less, and that the porosity according to the ASTM standard is extra coarse, so that saline can be smoothly supplied to the superabsorbent resin during measurement.
[0039] The cylinder 22 is a part where the superabsorbent polymer sample is applied, and has a mesh on the lower surface that contacts the glass filter and an open upper surface. The superabsorbent polymer is applied to the inside of the cylinder through the upper surface, i.e., on the mesh on the lower surface.
[0040] The mesh may have an opening of 100 μm or less, 80 μm or less, 60 μm or less, or 40 μm or less, and 25 μm or more, so that the mesh can absorb saline or act only as a support for the superabsorbent polymer without affecting the movement of saline. The thread diameter of the mesh, i.e., the thickness of the original thread, may be 25 μm or more, or 28 μm or more, and 80 μm or less, or 70 μm or less, or 50 μm or less.
[0041] The material of the mesh may be nylon or stainless steel, but is not limited thereto. Meshes made of various materials that are saltwater resistant and do not affect the measurement of the physical properties of the superabsorbent resin can be suitably used.
[0042] It is preferable that the inner diameter of the cylinder is not significantly different from the diameter of the glass filter, in order to reduce errors caused by evaporation of saline during measurement of physical properties. For example, the difference between the diameter of the cylinder and the diameter of the glass filter may be within 30% or within 25%. Alternatively, the diameter of the cylinder may be the same as the diameter of the glass filter.
[0043] The length of the cylinder is not limited, but is preferably 30 mm or more, or 40 mm or more, and 80 mm or less, or 60 mm or less, or 50 mm or less so that the highly absorbent resin can be uniformly applied.
[0044] The materials of the first water tank, second water tank, pipes, connecting pipes, cylinders, etc. that constitute the device are not particularly limited, and any material that is saltwater resistant can be suitably used. In addition, although the specifications of each part of the device are exemplified as above, they are merely examples and are not limiting, and the specifications of each part can be appropriately adjusted depending on the amount of sample used or the purpose of measurement, etc.
[0045] By using this device, the absorption rate, absorption capacity, and diffusion performance of a highly water-absorbent resin can be easily and accurately measured without applying pressure.
[0046] Specifically, the measurement of the physical properties of the superabsorbent resin using the above-mentioned physical property measuring device may be carried out through the following steps.
[0047] i) The cylinder is separated from the second water tank, and a highly water-absorbent resin is applied to the inside of the cylinder. ii) Separately, the first tank is filled with physiological saline (0.9 wt % NaCl aqueous solution) so that the entire interior of the second tank is filled, and the glass filter of the second tank is saturated with physiological saline. iii) When the glass filter of the second water tank is saturated with physiological saline, the initial weight of the first water tank is measured, and then the cylinder is placed on the glass filter. iv) After the cylinder is placed on the glass filter, the weight of the first water tank is continuously measured to obtain the amount of saline absorbed by the highly water-absorbent polymer and the absorption rate data.
[0048] The step i) is a step of preparing a sample. First, after separating the cylinder from the second water tank, the sample superabsorbent polymer is poured through the top of the cylinder so that the superabsorbent polymer is placed on the mesh on the bottom. If the superabsorbent polymer particles overlap each other, accurate data cannot be obtained, so make sure that they are uniformly dispersed.
[0049] The amount of the superabsorbent polymer sample may be, for example, 0.1 g to 2.0 g, or 0.5 g to 2.0 g, or 1.0 g to 2.0 g, and the particle size range of the sample is 150 μm to 850 μm.
[0050] Step ii) is a step of saturating the measuring device with physiological saline, in which physiological saline is supplied to the first water tank so that the glass filter of the second water tank is saturated. When the glass filter is saturated, iii) the initial weight of the first water tank is measured, and then the cylinder coated with the superabsorbent polymer is placed on the glass filter so that the lower surface (i.e., the mesh surface) is in contact with the glass filter.
[0051] In the above measurement method, the superabsorbent polymer starts absorbing the saline solution from the moment the cylinder is placed on the glass filter, and the amount of saline solution that is lost is supplied from the first tank to the second tank, causing the weight of the first tank to decrease. Therefore, the weight loss of the first tank can be regarded as the amount of saline solution C absorbed by the superabsorbent polymer.
[0052] In addition, the absorption rate V of the superabsorbent polymer can be calculated from the amount of physiological saline solution absorbed by the superabsorbent polymer per unit time.
[0053] During the measurement, the temperature of the air outside the device and the temperature of the saline solution are maintained within the range of 23° C. to 25° C. If the temperature of the air outside the device or the temperature of the saline solution exceeds the range, measurement errors may occur.
[0054] During the measurement, the outside air and the internal pressure of the first water tank are maintained at atmospheric pressure (760±50 mmHg). For example, as described above, the internal pressure can be maintained at atmospheric pressure by including a pipe as an air passage in the upper part of the first water tank.
[0055] Under the above conditions, after obtaining the amount of saline solution absorbed by the superabsorbent polymer and the absorption rate data, the maximum absorption rate (Vmax), the time at which the maximum absorption rate is reached (Tmax), and the amount of saline solution absorbed by the superabsorbent polymer for 5 minutes (C5min) can be derived, based on which the absorbency, absorption rate, rewetting and leakage prevention properties of the superabsorbent polymer can be accurately measured or predicted.
[0056] Manufacturing method of superabsorbent resin Examples of highly water-absorbent resins that satisfy the above physical properties include: A step (step 1) of polymerizing a monomer composition including a water-soluble ethylenically unsaturated monomer having an acidic group, an internal crosslinking agent, and a polymerization initiator to form a polymer in which the water-soluble ethylenically unsaturated monomer and the internal crosslinking agent are crosslinked and polymerized; A step of pulverizing the polymer (step 2); and (3) drying and pulverizing the pulverized polymer to produce superabsorbent resin particles. The compound represented by the following Chemical Formula 1 or a salt thereof may be added in an amount of 50 ppm to 7,000 ppm based on the water-soluble ethylenically unsaturated monomer before the grinding in step 2 or before the drying in step 3.
[0057] [ka]
[0058] In the above formula 1, A1, A2 and A3 each independently represent a single bond, a carbonyl,
[0059] [ka]
[0060] where at least one of these is carbonyl or
[0061] [ka]
[0062] wherein m1, m2, and m3 are each independently an integer from 1 to 8;
[0063] [ka]
[0064] are connected to adjacent oxygen atoms,
[0065] [ka]
[0066] are connected to adjacent R1, R2 and R3, respectively; R1, R2 and R3 are each independently hydrogen, linear or branched alkyl having 6 to 18 carbon atoms, or linear or branched alkenyl having 6 to 18 carbon atoms; n is an integer from 1 to 9.
[0067] The compound represented by Formula 1 or a salt thereof can act as a surfactant for a polymer. When the surfactant is added before the polymer is crushed or dried, a large amount of the surfactant is present on the surface of the polymer having a high water content, thereby reducing the high adhesion of the polymer and preventing excessive aggregation.
[0068] In addition, the hydrophobic functional group portion contained in the surfactant imparts hydrophobicity to the surface of the crushed superabsorbent resin particles, thereby reducing the friction between the particles and increasing the apparent density of the superabsorbent resin, while the hydrophilic functional group portion contained in the surfactant is also bonded to the superabsorbent resin particles, preventing a decrease in the surface tension of the resin.
[0069] In addition, by adjusting the amount of the surfactant to 50 ppm to 7,000 ppm based on the water-soluble ethylenically unsaturated monomer, the superabsorbent resin produced can satisfy the initial absorption rate and absorbency profile of i) to iii) described above.
[0070] As a result, the superabsorbent resin produced by the above-mentioned production method has a high apparent density value while exhibiting the same level of surface tension as resins that do not use surfactants, and can exhibit excellent absorption speed and absorption capacity without causing rewetting.
[0071] The term "polymer" or "polymeric polymer" as used in the present specification means a polymerized state of water-soluble ethylenically unsaturated monomers, and can encompass any range of moisture content or particle size.
[0072] In addition, the term "super absorbent polymer" refers to a crosslinked polymer or a base resin in the form of a powder consisting of super absorbent polymer particles obtained by pulverizing the crosslinked polymer depending on the context, or is used to encompass the crosslinked polymer or base resin that has been subjected to additional processes, such as drying, pulverization, classification, surface crosslinking, etc., to be in a state suitable for commercialization.
[0073] The term "fine powder" refers to superabsorbent resin particles having a particle size of less than 150 μm. The particle size of such resin particles may be measured according to the European Disposables and Nonwovens Association (EDANA) standard EDANA WSP 220.3 method.
[0074] Hereinafter, each step of the method for preparing a superabsorbent resin according to an embodiment will be described in detail.
[0075] Preparation of the monomer composition and polymerization step The polymerization step may include mixing a water-soluble ethylenically unsaturated monomer having an acidic group, an internal crosslinking agent, and a polymerization initiator to prepare a monomer composition, and polymerizing the monomer composition to form a polymer.
[0076] The water-soluble ethylenically unsaturated monomer may be any monomer commonly used in the manufacture of superabsorbent resins. As a non-limiting example, the water-soluble ethylenically unsaturated monomer may be a compound represented by the following formula 2:
[0077] [Chemical formula 2] R-COOM'
[0078] In the above formula 2, R is an alkyl group having 2 to 5 carbon atoms and containing an unsaturated bond, M' is a hydrogen atom, a monovalent or divalent metal, an ammonium group or an organic amine salt.
[0079] Preferably, the monomer may be one or more selected from the group consisting of (meth)acrylic acid, and monovalent (alkali) metal salts, divalent metal salts, ammonium salts and organic amine salts of these acids.
[0080] In this way, when (meth)acrylic acid and / or its salt is used as the water-soluble ethylenically unsaturated monomer, it is advantageous to obtain a superabsorbent resin with improved water absorption. In addition, as the monomer, maleic anhydride, fumaric acid, crotonic acid, itaconic acid, 2-acryloylethanesulfonic acid, 2-methacryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid or 2-(meth)acrylamido-2-methylpropanesulfonic acid, (meth)acrylamide, N-substituted (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, polyethylene glycol (meth)acrylate, (N,N)-dimethylaminoethyl (meth)acrylate, (N,N)-dimethylaminopropyl (meth)acrylamide, etc. may be used.
[0081] The water-soluble ethylenically unsaturated monomer having an acidic group can be used for polymerization in a state where it is partially neutralized with an alkaline substance such as sodium hydroxide, potassium hydroxide, ammonium hydroxide, etc. Specifically, in the step of preparing the monomer composition, the alkaline substance can be added as a neutralizing agent to neutralize at least a portion of the acidic group of the water-soluble ethylenically unsaturated monomer, and then polymerization can be started.
[0082] If the monomer is neutralized, the neutralization degree of the monomer may be 40 to 95 mol%, or 40 to 80 mol%, or 45 to 75 mol%. The range of the neutralization degree can be adjusted according to the final physical properties. If the neutralization degree of the monomer is too high, the neutralized monomer may precipitate and the polymerization may not proceed smoothly. Conversely, if the neutralization degree is too low, the absorbency of the polymer may be significantly reduced and the polymer may exhibit properties similar to elastic rubber, which is difficult to handle.
[0083] Alternatively, the water-soluble ethylenically unsaturated monomer may be used in the polymerization in a state in which the acidic groups are not neutralized.
[0084] Water-soluble ethylenically unsaturated monomers (e.g., acrylic acid) in which the acid group is not neutralized are in a liquid state at room temperature and have high miscibility with the solvent (water), so they exist in the form of a mixed solution in the monomer composition. However, water-soluble ethylenically unsaturated monomers in which the acid group is neutralized are in a solid state at room temperature and have different solubility depending on the temperature of the solvent (water), with the solubility decreasing as the temperature decreases.
[0085] As described above, the water-soluble ethylenically unsaturated monomer in which the acidic group is not neutralized has a higher solubility or miscibility in a solvent (water) than a monomer in which the acidic group is neutralized, and therefore does not precipitate even at low temperatures, which is advantageous for long-term polymerization at low temperatures. As a result, a polymer having a higher molecular weight and a uniform molecular weight distribution can be stably formed by performing long-term polymerization using the water-soluble ethylenically unsaturated monomer in which the acidic group is not neutralized.
[0086] In addition, it is possible to form a polymer having a longer chain than when a water-soluble ethylenically unsaturated monomer in which the acid group is not neutralized is used, and it is possible to achieve the effect of reducing the content of water-soluble components that exist in an uncrosslinked state due to incomplete polymerization or crosslinking.
[0087] In this way, when polymerization is first carried out in a state in which the acidic groups of the monomers are not neutralized, a step of adding a neutralizing agent to the polymer after the polymerization step to neutralize at least a portion of the acidic groups can be carried out.
[0088] In this case, as the neutralizing agent, an alkaline substance such as the above-mentioned sodium hydroxide, potassium hydroxide, or ammonium hydroxide may be used.
[0089] In addition, the degree of neutralization, which refers to the degree to which the acidic groups in the polymer are neutralized by the neutralizing agent, may be 50 to 90 mol%, or 60 to 85 mol%, or 65 to 85 mol%, or 65 to 75 mol%. The range of the degree of neutralization may vary depending on the final properties, but if the degree of neutralization is too high, the absorption capacity of the superabsorbent resin may decrease, and the concentration of carboxyl groups on the particle surface may be too low, making it difficult to perform surface cross-linking in the subsequent process, and the absorption characteristics or liquid permeability under pressure may decrease. On the other hand, if the degree of neutralization is too low, not only the absorption capacity of the polymer may be significantly reduced, but it may also exhibit properties similar to elastic rubber, which is difficult to handle.
[0090] Meanwhile, the concentration of the water-soluble ethylenically unsaturated monomer in the monomer composition may be appropriately adjusted in consideration of the polymerization time and reaction conditions, and may be about 20 to about 60% by weight, or about 20 to about 40% by weight, regardless of whether or not it is neutralized.
[0091] The term "internal crosslinking agent" used in this specification is a term used to distinguish it from a surface crosslinking agent for crosslinking the surface of a superabsorbent resin particle described later, and plays a role of introducing a crosslinking bond between unsaturated bonds of the water-soluble ethylenically unsaturated monomer described above to form a polymer containing a crosslinked structure.
[0092] The crosslinking in this step is performed regardless of whether it is on the surface or inside. However, when the surface crosslinking process of the superabsorbent resin particles described below is performed, the surface of the finally produced superabsorbent resin particles may include a newly crosslinked structure by the surface crosslinking agent, and the inside of the superabsorbent resin particles may maintain the structure crosslinked by the internal crosslinking agent.
[0093] According to an embodiment of the present invention, the internal crosslinking agent may include at least one of a multifunctional acrylate-based compound, a multifunctional allyl-based compound, or a multifunctional vinyl-based compound.
[0094] Non-limiting examples of the polyfunctional acrylate compound include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, butanediol di(meth)acrylate, butylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, pentaerythritol, Examples of the acrylates include dipentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol di(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, glycerin di(meth)acrylate, and glycerin tri(meth)acrylate, and these may be used alone or in combination of two or more.
[0095] Non-limiting examples of the polyfunctional allyl compounds include ethylene glycol diallyl ether, diethylene glycol diallyl ether, triethylene glycol diallyl ether, tetraethylene glycol diallyl ether, polyethylene glycol diallyl ether, propylene glycol diallyl ether, tripropylene glycol diallyl ether, polypropylene glycol diallyl ether, butanediol diallyl ether, butylene glycol diallyl ether, hexanediol diallyl ether, pentaerythritol diallyl ether, pentaerythritol triallyl ether, pentaerythritol tetraallyl ether, dipentaerythritol diallyl ether, dipentaerythritol triallyl ether, dipentaerythritol tetraallyl ether, dipentaerythritol pentaallyl ether, trimethylolpropane diallyl ether, trimethylolpropane triallyl ether, glycerin diallyl ether, and glycerin triallyl ether. These may be used alone or in combination of two or more.
[0096] Non-limiting examples of polyfunctional vinyl compounds include ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, tetraethylene glycol divinyl ether, polyethylene glycol divinyl ether, propylene glycol divinyl ether, tripropylene glycol divinyl ether, polypropylene glycol divinyl ether, butanediol divinyl ether, butylene glycol divinyl ether, hexanediol divinyl ether, pentaerythritol divinyl ether, pentaerythritol trivinyl ether, pentaerythritol tetravinyl ether, dipentaerythritol divinyl ether, dipentaerythritol trivinyl ether, dipentaerythritol tetravinyl ether, dipentaerythritol pentavinyl ether, trimethylolpropane divinyl ether, trimethylolpropane trivinyl ether, glycerin divinyl ether, and glycerin trivinyl ether, which may be used alone or in combination of two or more. Preferably, pentaerythritol triallyl ether may be used.
[0097] The above-mentioned polyfunctional allyl compounds or polyfunctional vinyl compounds can form a crosslinked structure during the polymerization process by bonding two or more unsaturated groups contained in the molecule with the unsaturated bonds of the water-soluble ethylenically unsaturated monomer or with the unsaturated bonds of other internal crosslinking agents, and unlike acrylate compounds containing an ester bond (-(C=O)O-) in the molecule, the crosslinked bonds can be more stably maintained even during the neutralization process after the above-mentioned polymerization reaction.
[0098] This increases the gel strength of the produced superabsorbent resin, improving process stability during the extrusion process after polymerization, and minimizing the amount of water-soluble matter.
[0099] The crosslinking polymerization of the water-soluble ethylenically unsaturated monomer in the presence of such an internal crosslinking agent may be carried out in the presence of a polymerization initiator, and, if necessary, a thickener, a plasticizer, a storage stabilizer, an antioxidant, etc.
[0100] In the monomer composition, the internal crosslinking agent may be used in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. For example, the internal crosslinking agent may be used in an amount of 0.01 parts by weight or more, or 0.05 parts by weight or more, or 0.1 parts by weight or more, and 5 parts by weight or less, or 3 parts by weight or less, or 2 parts by weight or less, or 1 part by weight or less, or 0.7 parts by weight or less based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. If the content of the upper internal crosslinking agent is too low, crosslinking may not occur sufficiently, making it difficult to realize strength above an appropriate level, and if the content of the internal crosslinking agent is too high, the internal crosslinking density may increase, making it difficult to realize the desired water retention ability.
[0101] The polymer formed using such an internal crosslinking agent has a three-dimensional network structure in which the main chain formed by polymerization of the water-soluble ethylenically unsaturated monomer is crosslinked by the internal crosslinking agent. When the polymer has a three-dimensional network structure, the water retention capacity and pressure absorption capacity, which are various physical properties of the superabsorbent resin, can be significantly improved compared to a two-dimensional linear structure that is not additionally crosslinked by the internal crosslinking agent.
[0102] According to an embodiment of the present invention, the step of polymerizing the monomer composition to form a polymer may be performed in a batch type reactor.
[0103] In a typical method for producing a superabsorbent resin, the polymerization method is largely divided into thermal polymerization and photopolymerization depending on the polymerization energy source. In general, when thermal polymerization is performed, it may be performed in a reactor having a stirring shaft such as a kneader, and when photopolymerization is performed, it may be performed in a reactor equipped with a movable conveyor belt or in a vessel with a flat bottom.
[0104] Meanwhile, the above polymerization methods generally have a short polymerization reaction time (eg, 1 hour or less), so that the molecular weight of the polymer is not large and the polymer has a broad molecular weight distribution.
[0105] On the other hand, when photopolymerization is carried out in a reactor equipped with a movable conveyor belt or a flat-bottomed vessel, the morphology of the hydrogel polymer obtained is usually a hydrogel polymer on a sheet having the width of the belt, and the thickness of the polymer sheet varies depending on the concentration of the monomer composition injected and the injection speed or amount, but is usually about 0.5 to about 5 cm.
[0106] However, if the monomer composition is supplied so that the thickness of the polymer on the sheet is too thin, production efficiency is low, which is not preferable, and if the thickness of the polymer on the sheet is increased for productivity, the polymerization reaction does not occur uniformly throughout the entire thickness, making it difficult to form a high-quality polymer.
[0107] In addition, the polymerization in the reactor having a reactor agitator equipped with a conveyor belt is performed in a continuous manner in which new monomer composition is supplied to the reactor while the polymerization result is moving, and therefore polymers with different polymerization rates are mixed together. As a result, it is difficult to perform uniform polymerization throughout the monomer composition, which may result in a deterioration in overall physical properties.
[0108] However, according to one embodiment of the present invention, the polymerization is carried out in a batch reactor in a fixed bed mode, so that the risk of polymers having different polymerization rates being mixed together is reduced, and thus a polymer having uniform quality can be obtained.
[0109] In addition, the polymerization step is carried out in a batch reactor having a predetermined volume, and the polymerization reaction is carried out for a longer time, for example, 3 hours or more, than in the case of carrying out continuous polymerization in a reactor equipped with a conveyor belt. Despite the long polymerization reaction time, since the polymerization is carried out on unneutralized water-soluble ethylenically unsaturated monomer, the monomer does not precipitate well even if the polymerization is carried out for a long time, and therefore, it is advantageous for long-term polymerization.
[0110] On the other hand, the polymerization in the batch reactor of the present invention uses a thermal polymerization method, and thus the polymerization initiator is a thermal polymerization initiator.
[0111] The thermal polymerization initiator may be one or more selected from the group consisting of persulfate initiators, azo initiators, hydrogen peroxide, and ascorbic acid. Specifically, examples of persulfate initiators include sodium persulfate (Na2S2O8), potassium persulfate (K2S2O8), and ammonium persulfate ((NH4)2S2O8). Examples of azo initiators include 2,2-azobis(2-amidinopropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene)isobutyramidine dihydrochloride, and the like. dihydrochloride, 2-(carbamoylazo)isobutylonitrile, 2,2-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, 4,4-azobis-(4-cyanovaleric acid), etc. More various thermal polymerization initiators are described in detail in Odian's book "Principle of Polymerization" (Wiley, 1981), p. 203, and are not limited to the above-mentioned examples.
[0112] The polymerization initiator may be used in an amount of 2 parts by weight or less relative to 100 parts by weight of the water-soluble ethylenically unsaturated monomer. In other words, if the concentration of the polymerization initiator is too low, the polymerization rate may be slowed down, and a large amount of residual monomer may be extracted in the final product, which is not preferable. On the other hand, if the concentration of the polymerization initiator is higher than the above range, the polymer chain forming the network becomes shorter, the content of water-soluble components increases, and the physical properties of the resin, such as the compression absorption capacity, may decrease, which is not preferable.
[0113] Meanwhile, in one embodiment of the present invention, the polymerization can be initiated by adding a reducing agent that forms a redox couple with the initiator.
[0114] Specifically, the initiator and the reducing agent react with each other to form radicals when introduced into the polymer solution.
[0115] The formed radicals react with the monomer, and the oxidation-reduction reaction between the initiator and the reducing agent is highly reactive, so polymerization can be initiated even with only a small amount of initiator and reducing agent added, making it possible to perform low-temperature polymerization without the need to increase the process temperature, and minimizing changes in the physical properties of the polymer solution.
[0116] The polymerization reaction using the oxidation-reduction reaction can be smoothly carried out at or below room temperature (25° C.) For example, the polymerization reaction may be carried out at a temperature of 5° C. to 25° C., or 5° C. to 20° C.
[0117] In an embodiment of the present invention, when a persulfate initiator is used as the initiator, the reducing agent may be at least one selected from the group consisting of sodium metabisulfite (Na2S2O5); tetramethylethylenediamine (TMEDA); a mixture of iron(II) sulfate and EDTA (FeSO4 / EDTA); sodium formaldehyde sulfoxylate; and disodium 2-hydroxy-2-sulfinoacteate.
[0118] As an example, potassium persulfate may be used as the initiator and disodium 2-hydroxy-2-sulfinoacetate as the reducing agent, or ammonium persulfate may be used as the initiator and tetramethylethylenediamine as the reducing agent, or sodium persulfate may be used as the initiator and sodium formaldehyde sulfoxylate as the reducing agent.
[0119] In another embodiment of the present invention, when a hydrogen peroxide-based initiator is used as the initiator, the reducing agent may be at least one selected from the group consisting of ascorbic acid; sucrose; sodium sulfite (Na2SO3), sodium metabisulfite (Na2S2O5); tetramethylethylenediamine (TMEDA); a mixture of iron(II) sulfate and EDTA (FeSO4 / EDTA); sodium formaldehyde sulfoxylate; disodium 2-hydroxy-2-sulfinoacteate; and disodium 2-hydroxy-2-sulfoacteate.
[0120] The monomer composition may further contain additives such as a thickener, a plasticizer, a storage stabilizer, and an antioxidant, if necessary.
[0121] The monomer composition including the monomer may be in a solution state dissolved in a solvent such as water, and the solid content of the monomer composition in such a solution state, i.e., the concentration of the monomer, the internal crosslinking agent, and the polymerization initiator, may be appropriately adjusted in consideration of the polymerization time, reaction conditions, etc. For example, the solid content in the monomer composition may be 10 to 80 wt%, or 15 to 60 wt%, or 30 to 50 wt%.
[0122] In this case, the solvent used is not limited in composition as long as it can dissolve the above-mentioned components, and may be used in combination with one or more selected from, for example, water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butanediol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate, and N,N-dimethylacetamide.
[0123] The polymer obtained by this method can form a polymer having a high molecular weight and a uniform molecular weight distribution as described above by polymerizing an unneutralized ethylenically unsaturated monomer, and can reduce the content of water-soluble components.
[0124] The polymer obtained by such a method may be in a hydrogel polymer state with a water content of 30 to 80% by weight. For example, the water content of the polymer may be 30% by weight or more, or 45% by weight or more, or 50% by weight or more, and 80% by weight or less, or 70% by weight or less, or 60% by weight or less.
[0125] If the moisture content of the polymer is too low, it may be difficult to ensure an adequate surface area in the subsequent grinding step, and therefore the polymer may not be effectively ground. If the moisture content of the polymer is too high, the pressure applied in the subsequent grinding step may increase, making it difficult to grind the polymer to the desired particle size.
[0126] Meanwhile, throughout this specification, the term "moisture content" refers to the amount of moisture in the total polymer weight, which is calculated by subtracting the weight of the polymer in a dry state from the weight of the polymer. Specifically, it is defined as a value calculated by measuring the weight loss due to the evaporation of moisture in the polymer during the process of drying by increasing the temperature of the crumb-state polymer through infrared heating. In this case, the drying conditions are a method of increasing the temperature to about 180°C at room temperature and then maintaining it at 180°C, and the total drying time is set to 40 minutes, including a 5-minute temperature increase step, and the moisture content is measured.
[0127] Polymer grinding step Next, the hydrogel polymer having a water content of 30 to 80 wt % is pulverized. In this process, the polymer may be simultaneously chopped and aggregated, and the secondary aggregate particles formed by aggregating the chopped polymer have a significantly increased surface area, which can significantly improve the absorption rate.
[0128] The step of grinding the polymer may be carried out after the compound represented by Formula 1 or a salt thereof is added to the polymer.
[0129] The compound represented by the above Chemical Formula 1 or a salt thereof is used as a surfactant that inhibits aggregation of highly water-absorbent resin particles.
[0130] The surfactant represented by the above formula 1 is a non-ionic surfactant and has excellent surface adsorption performance due to hydrogen bonding even with unneutralized polymers, and is therefore suitable for realizing the desired aggregation control effect. On the other hand, in the case of an anionic surfactant that is not a non-ionic surfactant, when it is mixed with a polymer neutralized with a neutralizing agent such as NaOH or Na2SO4, the ionized Na is attached to the carboxyl group substituent of the polymer. + When the compound is adsorbed via ions and mixed with an unneutralized polymer, there is a problem that the adsorption efficiency to the polymer is relatively reduced due to competition with the anions of the carboxyl group substituents of the polymer.
[0131] Specifically, in the surfactant represented by the above chemical formula 1, the hydrophobic functional groups are the terminal functional groups R1, R2, and R3 (if they are not hydrogen), and the hydrophilic functional groups are the portion derived from glycerol in the chain and the terminal hydroxyl group (A n is a single bond and at the same time R n is hydrogen, n=1 to 3), the glycerol-derived portion and the terminal hydroxyl group are hydrophilic functional groups that play a role in improving the adsorption performance to the polymer surface, thereby effectively suppressing the aggregation of the superabsorbent resin particles.
[0132] In the above formula 1, the hydrophobic functional groups R1, R2, and R3 (when not hydrogen) are each independently a straight or branched alkyl having 6 to 18 carbon atoms or a straight or branched alkenyl having 6 to 18 carbon atoms. In this case, when the R1, R2, and R3 (when not hydrogen) are alkyl or alkenyl having less than 6 carbon atoms, there is a problem that the aggregation control of the pulverized particles is not effectively performed due to the short chain length, and when the R1, R2, and R3 (when not hydrogen) are alkyl or alkenyl having more than 18 carbon atoms, there is a problem that the mobility of the surfactant is reduced and it may not be effectively mixed with the polymer, and the unit cost of the composition may become high due to the increase in the cost of the surfactant.
[0133] Preferably, R1, R2, and R3 are hydrogen, or in the case of a linear or branched alkyl having 6 to 18 carbon atoms, they may be 2-methylhexyl, n-heptyl, 2-methylheptyl, n-octyl, n-nonyl, n-decanyl, n-undecanyl, n-dodecanyl, n-tridecanyl, n-tetradecanyl, n-pentadecanyl, n-hexadecanyl, n-heptadecanyl, or n-octadecanyl, or in the case of a linear or branched alkenyl having 6 to 18 carbon atoms, they may be 2-hexenyl, 2-heptenyl, 2-octenyl, 2-nonenyl, n-dekenyl, 2-undekenyl, 2-dodekenyl, 2-tridekenyl, 2-tetradekenyl, 2-pentadekenyl, 2-hexadekenyl, 2-heptadekenyl, or 2-octadekenyl.
[0134] The surfactant may be selected from compounds represented by the following formulas 1-1 to 1-14.
[0135] [ka] [ka] [ka]
[0136] Meanwhile, the surfactant may be used in an amount of 50 ppm to 7,000 ppm based on the water-soluble ethylenically unsaturated monomer. If the surfactant is used too little, it may not be uniformly adsorbed on the polymer surface, so that re-aggregation of particles may occur after grinding or drying, and if the surfactant is used too much, various physical properties of the final superabsorbent resin may be deteriorated. For example, the surfactant may be used in an amount of 50 ppm or more, 100 ppm or more, 150 ppm or more, or 1,000 ppm or more, and 7,000 ppm or less, 6,000 ppm or less, 5,000 ppm or less, 4,000 ppm or less, or 3,000 ppm or less based on the water-soluble ethylenically unsaturated monomer.
[0137] The method of mixing such a surfactant with a polymer is not particularly limited as long as it can be uniformly mixed with the polymer, and can be appropriately selected and used. Specifically, the surfactant can be mixed in a dry state, dissolved in a solvent and then mixed in a solution state, or melted and then mixed.
[0138] Among these, for example, the surfactant may be mixed in a state of solution dissolved in a solvent. In this case, any type of solvent may be used without being limited to an inorganic solvent or an organic solvent, but water is the most suitable in consideration of the ease of the drying process and the cost of the solvent recovery system. In addition, the solution may be mixed by putting the surfactant and the polymer in a reaction vessel, putting the polymer in a mixer and injecting the solution, or continuously supplying the polymer and the solution to a continuously operated mixer and mixing them.
[0139] When a monomer in which a part of the acidic groups is neutralized is used in the step 1, the step 2 is carried out subsequent to the step 1.
[0140] On the other hand, when a non-neutralized monomer is used in step 1, a step of neutralizing at least a part of the acidic groups contained in the polymer may be carried out as described above, and the neutralization step and the polymer grinding step may be carried out simultaneously or sequentially.
[0141] Specifically, a neutralizing agent may be added to the polymer to neutralize the acidic groups, and then a surfactant may be added to the neutralized polymer to pulverize the polymer mixed with the surfactant, or a neutralizing agent and a surfactant may be added simultaneously to the polymer to neutralize and pulverize the polymer. Alternatively, a surfactant may be added first and then a neutralizing agent may be added later. Alternatively, a neutralizing agent and a surfactant may be added alternately. Alternatively, a surfactant may be added first and pulverized, and then a neutralizing agent may be added to neutralize the neutralized hydrogel polymer, and a pulverization process may be performed by adding an additional surfactant to the neutralized hydrogel polymer. Meanwhile, it is preferable to provide a certain time lag between the addition of the neutralizing agent and the pulverization process in order to uniformly neutralize the entire polymer.
[0142] At least a portion or a substantial amount of the surfactant may be present on the surface of the hydrogel polymer particles.
[0143] Here, the fact that the surfactant is present on the surface of the hydrogel polymer particles means that at least a part or a substantial amount of the surfactant is adsorbed or bound to the surface of the hydrous superabsorbent resin particles. Specifically, the surfactant may be physically or chemically adsorbed to the surface of the superabsorbent resin. More specifically, the hydrophilic functional group of the surfactant may be physically adsorbed to the hydrophilic portion of the surface of the superabsorbent resin by intermolecular forces such as dipole-dipole interaction. In this way, the hydrophilic portion of the surfactant physically adsorbs to the surface of the superabsorbent resin particles to surround the surface, and the hydrophobic portion of the surfactant does not adsorb to the surface of the resin particles, so that the resin particles may be coated with the surfactant in the form of a kind of micelle structure. This is because the surfactant is not added during the polymerization process of the water-soluble ethylenically unsaturated monomer, but is added in the pulverization step after the formation of the polymer, and therefore the surfactant can faithfully perform its role as a surfactant compared to the case where the surfactant is added during the polymerization process and exists inside the polymer, and particles with a large surface area can be obtained in the form of an aggregate of fine particles due to simultaneous pulverization and aggregation.
[0144] The grinding step may be carried out two or more times.
[0145] The type of the pulverizer used for the pulverization is not particularly limited, and specifically, the pulverizer may include any one selected from the group of pulverizing equipment consisting of a vertical pulverizer, a turbo cutter, a turbo grinder, a rotary cutter mill, a cutter mill, a disc mill, a shred crusher, a crusher, a chopper, and a disc cutter.
[0146] Alternatively, according to one embodiment of the present invention, the pulverization may be performed by a pulverizing device including a body portion including a transfer space into which the polymer is transferred, a screw member rotatably installed within the transfer space to move the polymer, a driving motor to provide a rotational driving force to the screw member, a cutter member installed in the body portion to pulverize the polymer, and a perforated plate having a plurality of holes formed therein and discharging the polymer pulverized by the cutter member to the outside of the body portion. In this case, the size of the holes provided in the perforated plate of the pulverizing device may be 1 mm to 20 mm, 5 mm to 15 mm, or 5 mm to 12 mm.
[0147] When the polymer is pulverized by controlling the aggregation of the polymer using such a pulverizing device, a smaller particle size distribution (a particle size of several tens to several hundreds of micrometers) is realized, and the subsequent drying and pulverization processes can be performed under milder conditions, thereby preventing the generation of fine powder and improving the physical properties of the superabsorbent resin.
[0148] Polymer drying and grinding steps The pulverized polymer is then dried and pulverized to produce highly water-absorbent resin particles.
[0149] In this case, the compound represented by the above Chemical Formula 1 or a salt thereof may be added to the polymer as a surfactant before the drying step.
[0150] The surfactant is as described above.
[0151] The drying step may be carried out so that the moisture content of the superabsorbent resin is 20% by weight or less, or 15% by weight or less, and 1% by weight or more, or 3% by weight or more.
[0152] For this reason, the temperature in the dryer used in the drying step may be about 150° C. or less, for example, about 80° C. to about 150° C., and may be relatively low. If the temperature in the dryer is too low, the drying time may be too long, and if the drying temperature is too high, a superabsorbent resin having a moisture content lower than the desired moisture content is obtained.
[0153] In this case, the drying may be performed in a moving type in which the material moves during drying, or in a fixed-bed type in which the material does not move.
[0154] The fluidized drying method refers to a method of drying materials while mechanically stirring them. In this case, the direction in which the hot air passes through the materials may be the same as or different from the direction in which the materials circulate. Alternatively, the materials may be circulated inside the dryer, and a heat transfer fluid (heat transfer oil) may be passed through a separate pipe outside the dryer to dry the materials.
[0155] The fixed-bed drying method refers to a method in which the material to be dried is suspended on the bottom of a porous iron plate through which air can pass, and hot air passes from bottom to top to dry the material.
[0156] Next, a step of pulverizing the dried superabsorbent resin particles to produce superabsorbent resin particles is carried out.
[0157] Specifically, the pulverization step may be performed by pulverizing the dried superabsorbent resin particles to have a particle size of normal particle level, that is, a particle size of 150 μm to 850 μm.
[0158] The pulverizer used for this purpose may be specifically a vertical pulverizer, a turbo cutter, a turbo grinder, a rotary cutter mill, a cutter mill, a disc mill, a shred crusher, a crusher, a chopper, or a disc cutter, and is not limited to the above-mentioned examples.
[0159] Alternatively, the grinding machine may be a pin mill, a hammer mill, a screw mill, a roll mill, a disc mill, a jog mill, or the like, but is not limited to the above examples.
[0160] Additional steps The method may further include, after the step of drying and pulverizing the superabsorbent resin particles, classifying the pulverized superabsorbent resin particles according to particle size.
[0161] The method may further include a step of forming a surface cross-linked layer on at least a part of the surface of the superabsorbent resin particles in the presence of a surface cross-linking agent after crushing and / or classifying the superabsorbent resin particles. By the step, the cross-linked polymer contained in the superabsorbent resin particles is additionally cross-linked via the surface cross-linking agent, and a surface cross-linked layer can be formed on at least a part of the surface of the superabsorbent resin particles.
[0162] The surface cross-linking agent may be any of the surface cross-linking agents used in the manufacture of existing superabsorbent resins without any particular limitation.For example, the surface cross-linking agent may include one or more polyols selected from the group consisting of ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 1,2-hexanediol, 1,3-hexanediol, 2-methyl-1,3-propanediol, 2,5-hexanediol, 2-methyl-1,3-pentanediol, 2-methyl-2,4-pentanediol, tripropylene glycol and glycerol; one or more carbonate-based compounds selected from the group consisting of ethylene carbonate, propylene carbonate and glycerol carbonate; epoxy compounds such as ethylene glycol diglycidyl ether; oxazoline compounds such as oxazolidinone; polyamine compounds; mono-, di- or polyoxazolidinone compounds; or cyclic urea compounds; etc.
[0163] Specifically, one or more, two or more, or three or more of the above-mentioned surface crosslinking agents may be used as the surface crosslinking agent. For example, ethylene carbonate-propylene carbonate (ECPC), propylene glycol, and / or glycerol carbonate may be used.
[0164] The surface cross-linking agent may be used in an amount of about 0.001 to about 5 parts by weight based on 100 parts by weight of the superabsorbent resin particles. For example, the surface cross-linking agent may be used in an amount of 0.005 parts by weight or more, or 0.01 parts by weight or more, or 0.05 parts by weight or more, or 5 parts by weight or less, or 4 parts by weight or less, or 3 parts by weight or less based on 100 parts by weight of the superabsorbent resin particles. By adjusting the content range of the surface cross-linking agent within the above range, a superabsorbent resin exhibiting excellent absorption properties can be produced.
[0165] The step of forming the surface cross-linked layer may be performed by adding an inorganic substance to the surface cross-linking agent. That is, the step of forming the surface cross-linked layer by additionally cross-linking the surface of the highly water-absorbent resin particles in the presence of the surface cross-linking agent and the inorganic substance can be performed.
[0166] The inorganic material may be one or more inorganic materials selected from the group consisting of silica, clay, alumina, silica-alumina composite, titania, zinc oxide, and aluminum sulfate. The inorganic material may be used in powder or liquid form, and in particular, alumina powder, silica-alumina powder, titania powder, or nanosilica solution may be used. The inorganic material may be used in an amount of about 0.001 to about 1 part by weight based on 100 parts by weight of the superabsorbent resin particles.
[0167] In addition, there is no limitation on the configuration of the method for mixing the surface cross-linking agent with the superabsorbent resin composition. For example, a method of mixing the surface cross-linking agent and the superabsorbent resin composition in a reaction tank, a method of spraying the surface cross-linking agent into the superabsorbent resin composition, a method of continuously supplying the superabsorbent resin composition and the surface cross-linking agent to a continuously operated mixer, and the like may be used.
[0168] When the surface cross-linking agent and the superabsorbent polymer composition are mixed, water and methanol may be added together. When water and methanol are added, there is an advantage that the surface cross-linking agent can be uniformly dispersed in the superabsorbent polymer composition. At this time, the content of the added water and methanol can be appropriately adjusted to induce uniform dispersion of the surface cross-linking agent, prevent aggregation of the superabsorbent polymer composition, and optimize the surface penetration depth of the cross-linking agent.
[0169] The surface cross-linking process may be carried out at a temperature of about 80° C. to about 250° C. More specifically, the surface cross-linking process may be carried out at a temperature of about 100° C. to about 220° C., or about 120° C. to about 200° C., for about 20 minutes to about 2 hours, or about 40 minutes to about 80 minutes. When the above conditions for the surface cross-linking process are satisfied, the surface of the highly absorbent resin particles is sufficiently cross-linked, and the absorbency under pressure can be increased.
[0170] The temperature raising means for the surface crosslinking reaction is not particularly limited. Heating can be performed by supplying a heat medium or directly supplying a heat source. In this case, the type of heat medium that can be used may be a heated fluid such as steam, hot air, or hot oil, but is not limited thereto, and the temperature of the heat medium to be supplied can be appropriately selected in consideration of the means of the heat medium, the heating rate, and the target temperature of the heat raising. On the other hand, the heat source to be directly supplied includes heating through electricity and heating through gas, but is not limited to the above-mentioned examples.
[0171] According to an embodiment of the present invention, after the step of forming a surface cross-linked layer on at least a part of the surface of the superabsorbent resin particles, the method may further include at least one of a cooling step of cooling the superabsorbent resin particles having the surface cross-linked layer, a hydration step of adding water to the superabsorbent resin particles having the surface cross-linked layer, and a post-treatment step of adding an additive to the superabsorbent resin particles having the surface cross-linked layer. At this time, the cooling step, the hydration step, and the post-treatment step may be performed sequentially or simultaneously.
[0172] The additives added in the post-treatment step may include, but are not limited to, a liquid permeability improver, an anti-caking agent, a flowability improver, and an antioxidant.
[0173] By selectively carrying out the cooling step, the hydration step, and the post-treatment step, the moisture content of the final superabsorbent polymer can be increased, and a higher quality superabsorbent polymer product can be produced. EXAMPLES
[0174] Hereinafter, preferred examples will be presented to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the present invention and the technical spirit thereof. Naturally, such changes and modifications fall within the scope of the appended claims.
[0175] [Example] Comparative Example 1 (Polymer production step) A neutralization solution was prepared by mixing 488.5 g of acrylic acid, 663.5 g of 31.5 wt % NaOH aqueous solution, and 375 g of water in a glass reactor. A monomer composition was prepared by mixing 2000 ppm of polyethylene glycol diacrylate (PEGDA) as an internal crosslinking agent, 80 ppm of bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (Irgacure® 819) as an initiator, and 2000 ppm of sodium persulfate (SPS) with the neutralization solution based on the total weight of acrylic acid.
[0176] The monomer composition was placed in a square reaction vessel measuring 30 cm in width and 30 cm in length, and exposed to 10 mW / cm 2 The mixture was irradiated with ultraviolet light having an intensity of 1000 nm for 60 seconds to carry out a polymerization reaction, thereby obtaining a hydrogel polymer.
[0177] (Crushing step) The hydrogel polymer prepared in step 1 was cut into pieces measuring 5 cm in width and 5 cm in length, and the hydrogel was crushed using a meat chopper, which is a screw-type cutter. At this time, the screw-type cutter was equipped with a porous plate having a plurality of small holes with a hole size of 16 mm.
[0178] (Drying step) Then, 1,000 g of the pulverized superabsorbent resin hydrogel was placed in a ventilated dryer equipped with a perforated plate. Drying was carried out for 40 minutes while maintaining the internal temperature of the dryer at 180° C. to obtain a resin powder. The obtained powder was passed through a two-stage roll mill to obtain a base resin (BR) powder.
[0179] (Crushing and classification steps) The base resin was pulverized using a two-stage roll mill (GRAN-U-LIZER™, MPE) to give particles having a particle size of 150 μm to 850 μm.
[0180] The ground material was subjected to a classification to selectively recover only base resin particles having a particle size of 150 μm to 850 μm.
[0181] (Surface cross-linking step) A surface crosslinking liquid was prepared by mixing 5 g of water, 5.3 g of propylene glycol, 0.1 g of ethylene glycol diglycidyl ether, and 0.87 g of a 23 wt % aqueous aluminum sulfate solution with 100 g of the base resin particles obtained above, and the mixture was mixed for 2 minutes. The surface crosslinking reaction was carried out at 130° C. for 50 minutes to produce a final highly water absorbent resin.
[0182] Example 1 (Polymer production step) In a 10L glass vessel equipped with a stirrer and a thermometer, 1500g of acrylic acid, 6.3g of pentaerythritol triallyl ether as an internal crosslinking agent, and 3387g of water were stirred and mixed while maintaining the temperature at 5℃. Nitrogen was introduced into the glass vessel containing the mixture at 1000cc / min for 1 hour to replace the nitrogen condition. Next, 20.1g of 0.3% hydrogen peroxide aqueous solution, 22.5g of 1% ascorbic acid aqueous solution, and 45.0g of 2% 2,2'-azobis-(2-amidinopropane) dihydrochloric acid aqueous solution were added as polymerization initiators, and 22.3g of 0.01% iron sulfate aqueous solution was added as a reducing agent to start polymerization. After the temperature of the mixture reached 85℃, the mixture was polymerized at 90±2℃ for about 3 hours to obtain a polymer.
[0183] (Neutralization and grinding steps) The polymer was pulverized in a Micronizer (F200, Karl Schnell) equipped with a perforated plate containing a number of holes with a hole size of 10 mm at 1500 rpm by adding 5000 g of the polymer obtained. At this time, a 1.5 wt% aqueous solution of glycerol monolaurate (GML) was added so that the GML content relative to the acrylic acid was 1,000 ppm.
[0184] Then, the crushed polymer was fed into a meat chopper, a screw-type cutter equipped with a perforated plate containing a plurality of holes with a hole size of 6 mm, while rotating at 500 rpm, and the process of producing secondary agglomerated particles was repeated three times. In the first run, 220 g of 50 wt % NaOH aqueous solution was fed per 1000 g of polymer. In the second run, 39.3 g of 10 wt % Na2SO4 aqueous solution was fed per 1000 g of polymer after the first run. In the third run, the additive was not fed and water-containing superabsorbent resin particles were produced.
[0185] (Drying step) 1,000 g of the water-containing highly water-absorbent resin particles were dried for 40 minutes in a belt dryer at 120° C. to obtain a resin powder, which was then passed through a two-stage roll mill to obtain a base resin (BR) powder.
[0186] (Surface cross-linking step) Next, 100 g of the obtained base resin powder was mixed with 4 g of water, 6 g of methanol, 0.30 g of ethylene glycol diglycidyl ether (EJ-1030S), 0.1 g of propylene glycol, and 0.2 g of aluminum sulfate to prepare a surface cross-linking liquid, which was then mixed for 1 minute and subjected to a surface cross-linking reaction at 140°C for 50 minutes to obtain a surface cross-linked superabsorbent resin.
[0187] Example 2 A highly water-absorbent resin was produced in the same manner as in Example 1, except that in the neutralization and pulverization steps, a 1.5 wt % aqueous solution of GML was added so that the GML concentration relative to the acrylic acid was 5,000 ppm.
[0188] Comparative Example 2 A superabsorbent resin was produced in the same manner as in Example 1, except that in the neutralization and pulverization steps, a 1.5 wt % aqueous solution of GML was added so that the GML concentration relative to the acrylic acid was 20,000 ppm.
[0189] Experimental example 1: Measurement of the physical properties of superabsorbent resin The physical properties of each of the superabsorbent polymers in the Examples and Comparative Examples were measured by the following method using a superabsorbent polymer physical property measuring device 100 as shown in Fig. 1. The measurement temperature was maintained at 24°C.
[0190] The first water tank 10 was placed on a balance (13, A&D electronic balance GF-3000) connected to a computer for data collection, and a pipe 11 was provided to penetrate the top lid of the first water tank so that the internal pressure of the first water tank was maintained at the same as atmospheric pressure. The first water tank had an internal diameter of 10 cm, an internal height of 30 cm, and an internal volume of 2355 cm. 3 The tank used was a cylindrical acrylic tank, and the pipe was a glass pipe with a diameter of 1 cm and a height of 30 cm.
[0191] Separately, a second water tank 20 is provided, the inside width and length of the bottom surface being 20 cm, the inside height being 5 cm, and the inside volume being 2000 cm. 3 An acrylic aquarium tank was prepared with a glass filter 21 (Chemglass CG-201-52, diameter 80 mm, thickness 6.35 mm, extra coarse) attached to the center of the upper lid.
[0192] The second water tank was placed next to the balance, and connecting pipes 14 were provided at the lower part of the first water tank (at about 1 / 5 of the water tank height) and the lower part of the second water tank (at about 1 / 5 of the water tank height). A silicone tube with a diameter of 10 mm and a length of 50 cm was used as the connecting pipe.
[0193] Then, the first tank was filled with physiological saline (0.9 wt% sodium chloride aqueous solution) and the second tank was filled with physiological saline through the connecting tube. When the glass filter of the second tank was saturated with physiological saline, the initial weight of the first tank was measured.
[0194] Separately, a cylinder 22 made of polymethyl methacrylate was prepared, with an inner diameter of 60 mm and a height of 50 mm, and a 400 mesh stainless steel mesh (Material No. 1.4401 / AISI316mesh400, pore size 36μm, wire diameter 28μm) attached to the bottom and an open top. 1g of superabsorbent resin (23, particle size 150 to 850μm) was poured through the top of the cylinder, and the superabsorbent resin particles were evenly spread on the mesh so that they did not overlap each other. Immediately after the glass filter of the second water tank was saturated with physiological saline, the cylinder was placed on the glass filter so that the mesh was in contact with it.
[0195] Immediately after placing the cylinder on the glass filter, the weight of the first water tank was continuously collected using a computer. In other words, the amount of water absorbed by the superabsorbent polymer was measured from the weight loss of the first water tank, and the absorption rate V of the superabsorbent polymer was derived from the amount of water absorbed by the superabsorbent polymer per time (seconds). Data was collected until the superabsorbent polymer became saturated and could no longer reduce the weight of the first water tank, and the maximum absorption rate (Vmax), the time at which the maximum absorption rate was achieved (Tmax), and the amount of physiological saline absorbed by the superabsorbent polymer for 5 minutes were derived.
[0196] The measurement results are shown in Table 1 below. In the case of Comparative Example 2, the 5-minute absorption rate did not exceed 0.1 g / g sec, and instead rose and fell repeatedly with no clear peak being observed, making it impossible to derive Vmax and Tmax.
[0197] [Table 1]
[0198] Example 2: Manufacture and evaluation of absorbent cores Using the superabsorbent resins prepared in Example 1 and Comparative Example 1, absorbent cores were prepared in the following manner, and the absorption rate and rewet properties were measured.
[0199] (1) Manufacturing of absorbent cores Two sheets of airlaid paper (HungChin, 37 gsm) and one sheet of TABCW nonwoven fabric (Jinrou, 38 gsm) were cut to a size of 380 mm wide x 110 mm long. 5.8 g of superabsorbent polymer powder (particle size 150 to 850 μm) was applied onto the airlaid nonwoven fabric, and then the TABCW nonwoven fabric was layered on top of it. Another 5.8 g of superabsorbent polymer powder was applied, and then the airlaid nonwoven fabric was layered on top. Each layer was bonded with hot melt adhesive (a total of 8 gsm was used) to produce an absorbent core.
[0200] (2) Measurement of absorption rate 80 ml of saline solution (0.9 wt % sodium chloride solution) was injected into the absorbent core twice at 5-minute intervals, and the time it took for the saline solution to be completely absorbed and disappear from the core surface after each injection (absorption rate, seconds) was measured.
[0201] (3) Rewet measurement Twenty sheets of filter paper (Whatman, No. 4, 20-25 μm, diameter 110 mm) were prepared and their weights were measured.
[0202] One hour after the measurement of the physiological saline absorption rate in (2) was completed, 20 filter papers were placed on the absorption core and a pressure of 0.7 psi was applied for 1 minute. The weight of the filter papers was then measured, and the difference from the initial weight was calculated to measure the amount (g) of physiological saline that had seeped into the filter papers.
[0203] [Table 2]
[0204] From the above results, it can be confirmed that the superabsorbent resin of Example 1, which achieved a maximum absorption rate (Vmax) exceeding 0.4 g / g sec, a time at which the maximum absorption rate was reached (Tmax) exceeding 5 seconds or less than 120 seconds, and an amount of saline solution absorbed by the superabsorbent resin in 5 minutes (C5min) exceeding 40 g, not only exhibits an excellent absorption rate but also has significantly improved anti-rewetting properties compared to the superabsorbent resin of Comparative Example 1, which does not satisfy the above conditions. [Explanation of symbols]
[0205] 10: First tank 11: Pipe 12: Saline 13: Balance 14: Connecting pipe 20: Second tank 21: Glass filter 22: Cylinder 23:Super absorbent resin 100: Superabsorbent resin physical property measuring device
Claims
1. A superabsorbent polymer was applied to the surface of a porous substrate to which physiological saline (0.9 wt % NaCl aqueous solution) was continuously supplied, and the amount and absorption rate of physiological saline absorbed by the superabsorbent polymer from the surface of the porous substrate were continuously measured from the time when the superabsorbent polymer was applied. The maximum absorption rate (Vmax) exceeds 0.4 g / g sec; The time to achieve the maximum absorption rate (Tmax) is more than 5 seconds and less than 120 seconds; The amount of saline solution absorbed by the superabsorbent resin for 5 minutes (C5min) is more than 40 g. Super absorbent resin.
2. The maximum absorption rate (Vmax) is 0.45 g / g sec to 1 g / g sec; The highly water-absorbent resin according to claim 1.
3. The time to reach the maximum absorption rate (Tmax) is 8 to 40 seconds. The highly water-absorbent resin according to claim 1 or 2.
4. The amount of saline solution absorbed by the superabsorbent resin for 5 minutes (C5min) is 45g to 55g. The highly water-absorbent resin according to any one of claims 1 to 3.
Citation Information
Patent Citations
Biodegradable and highly absorbing resin composition, nonwoven fabric made from this composition and its use
JP1994306298A
Powdered cross-linked polymer capable of absorbing watery liquids and body fluids in the human body, method for producing the same and use thereof
JP1996509521A
Absorbing resin particle and manufacturing method thereof
JP2011190426A
Absorptive resin particle and absorptive article
JP2012012451A
Absorbing resin particles, process for producing same, and absorbent and absorbing article both including same
WO2010073658A1